2011
DOI: 10.1158/0008-5472.can-10-4552
|View full text |Cite|
|
Sign up to set email alerts
|

Small-Molecule Anticancer Compounds Selectively Target the Hemopexin Domain of Matrix Metalloproteinase-9

Abstract: Lack of target specificity by existing matrix metalloproteinase (MMP) inhibitors has hindered anti-metastatic cancer drug discovery. Inhibitors that bind to non-catalytic sites of MMPs and disrupt protease signaling function have the potential to be more specific and selective. In this work, compounds that target the hemopexin (PEX) domain of MMP-9 were identified using an in silico docking approach and evaluated using biochemical and biological approaches. Two of the selected compounds interfere with MMP-9-me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
123
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(129 citation statements)
references
References 42 publications
5
123
0
1
Order By: Relevance
“…Targeting the PEX9 domain is becoming an important focus for drug development, and a recent study (17) has identified a small-molecule compound that binds to PEX9 and inhibits carcinoma cell migration, proliferation, and metastasis. Using an in silico docking approach, these authors mapped the binding site of this compound to the central cavity of PEX9, in fact in close proximity to the VPLDTHDVFQ sequence identified in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting the PEX9 domain is becoming an important focus for drug development, and a recent study (17) has identified a small-molecule compound that binds to PEX9 and inhibits carcinoma cell migration, proliferation, and metastasis. Using an in silico docking approach, these authors mapped the binding site of this compound to the central cavity of PEX9, in fact in close proximity to the VPLDTHDVFQ sequence identified in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Two synthetic peptides (SRPQGPFL and NQVDQVGY) mimicking sequences in blade 1 and blade 4 of PEX9, respectively, were shown to affect MMP-9-CD44 interaction, MMP-9 dimerization, and migration of fibrosarcoma and carcinoma cells (16). A recent in silico approach has identified two small-molecule compounds that bind to PEX9 and inhibit tumor growth and metastasis (17). The isolated murine PEX9 on the other hand was shown to inhibit MMP-9 activity and invasion of melanoma cells (18), adhesion and migration of colorectal cancer cells (19), and angiogenesis and tumor growth in a glioblastoma model (20).…”
Section: B-cell Chronic Lymphocytic Leukemia (B-cll)mentioning
confidence: 99%
“…In both in vitro and in vivo systems, designed small molecules and peptides exert their inhibitory effects by preventing dimerization, thereby reducing tumor size, MMP-induced migration, and angiogenesis. [158][159][160] Promising studies have shown that these selective compounds could bind on specific sites for each MMP inside their hemopexin domain and prevent dimer-induced functions of several MMPs, including MMP14 and -9. [158][159][160][161][162] A more sophisticated approach proposed a bifunctional fusion protein able to bind and inactivate both the catalytic and hemopexin domains of MMP2.…”
Section: Targeting the Mmp Noncatalytic Domainmentioning
confidence: 99%
“…44). A latest report shows that small-molecule compounds that selectively target the hemopexin domain of MMP-9 can control tumor growth and inhibit lung metastasis in breast cancer xenograft model in mice (45). Moreover, VTN, an extracellular protein that interacts with many integrins, is also expressed highly in the liver, and was previously reported to be upregulated in primary hepatocellular carcinoma (46), or liver metastases from colorectal cancer (46,47) and neuroblastoma (48).…”
mentioning
confidence: 99%